The oral health of upper income Americans. (10th December 2015) - Bailit, Howard; Lim, Sungwoo; Ismail, Amid
Abstract: Background: Limited information is available on the oral health status of upper income Americans (>400 percent of the FPL). They constitute 33 percent of the population and account for 53 percent of dental expenditures. Methods: Using 1999‐2004 NHANES data, we examined differences in the mean number and percentage of decayed and filled permanent surfaces and missing teeth among age and family income groups. Results: For upper income Americans, across age groups, the mean number of untreated decayed surfaces and missing teeth ranged from 0.2 to 0.5 and 2.6 to 3.3, respectively. The mean number of restored surfaces was low in children but extensive in adults. Income disparities increased with increasing age. Discussion: Overall, upper income Americans have good oral health. Relatively few have untreated decayed surfaces or missing teeth. The reasons for the large number of restored surfaces in upper income adults require further research. Conclusion: Most upper income Americans are in good oral health, especially the 12‐18 year cohort. As this group ages, the oral health of upper income adults is expected to improve.